Bilateral optic nerve edema presenting as initial manifestation of thyroid eye disease. (2nd September 2016) - Wilson, Michelle E.; Kim, Charles; Carrasco, Jacqueline
ABSTRACT: A 48-year-old smoker with a history of hyperthyroidism treated 10 years prior to presentation with radioactive iodine ablation of the thyroid gland presented to his ophthalmologist with a 2-week history of transient loss of vision in the right eye occurring for 1 to 2 hours each morning. He denied ocular pain, diplopia or change in the prominence of one or both eyes. Examination revealed 2 mm of relative proptosis on the right, bilateral temporal flare and lower lid retraction. There was minimal upper lid retraction and no evidence of lid lag. Ocular motility was full. Dilated fundoscopic examination revealed bilateral optic nerve edema, right more than left. CT of the orbit demonstrated enlargement of the extraocular muscles bilaterally with marked enlargement of the right medial rectus and left inferior rectus muscles resulting in crowding at the orbital apex bilaterally. Laboratory testing revealed the patient to be hyperthyroid. The patient was treated with high dose oral steroids followed by orbital radiation. Hyperthyroidism was managed by the patient's primary care physician. Visual symptoms rapidly improved with oral steroids and orbital radiation. Optic nerve edema completely resolved. Repeat CT imaging demonstrated a reduction in the enlargement of the extraocular muscles with relief of bilateral optic nerve compression.